2013
DOI: 10.1177/0300060513484433
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a self-reported measure of medication adherence in patients with type 2 diabetes mellitus in Korea

Abstract: In light of acceptable reliability and validity, the MMAS-8 is a simple and quick method for the assessment of medication adherence among patient with type 2 diabetes mellitus, in a busy clinic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 21 publications
6
47
4
Order By: Relevance
“…The alpha coefficient reported in this study is lower than that reported for the scale among a patients with a mix of different chronic diseases in a Saudi Arabian study (0.795) (25). Compared with other translated versions of the MMAS-8 that were evaluated as measures for medication adherence in diabetes, the reported alpha value in this study was higher than those reported for the Malaysian (0.657) (21), Korean (0.66) (22) and Thai (0.61) (32) versions. However, the alpha coefficient for the Arabic version in the current study was lower than that reported for the original scale among patients diagnosed with hypertension (0.83) (10).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The alpha coefficient reported in this study is lower than that reported for the scale among a patients with a mix of different chronic diseases in a Saudi Arabian study (0.795) (25). Compared with other translated versions of the MMAS-8 that were evaluated as measures for medication adherence in diabetes, the reported alpha value in this study was higher than those reported for the Malaysian (0.657) (21), Korean (0.66) (22) and Thai (0.61) (32) versions. However, the alpha coefficient for the Arabic version in the current study was lower than that reported for the original scale among patients diagnosed with hypertension (0.83) (10).…”
Section: Discussioncontrasting
confidence: 78%
“…However, to some extent, the reported sensitivity was comparable to the sensitivity reported among diabetics for the same cut-off point score with the Malaysian (77.6%) (21) and Korean (74%) (22) versions but was higher than that reported with the Thai version (51%) (32). The reported sensitivity reflects a reasonable ability of the Arabic version to correctly identify type 2 diabetes patients who are low adherers to their medications, and it is deemed satisfactory especially considering the simplicity of the scale as a short self-reporting measure.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Patients showing high adherence score were classified into the adherence group and patients showing low or moderate adherence score into the non-adherence group. The Korean language version of MMAS-8 showed acceptable reliability and validity in a previous report [13]. In addition to MMAS-8, patients who missed a statin dose at least once were asked their reasons for missing the dose at each observation.…”
Section: Medication Adherencementioning
confidence: 94%
“…The MMAS-8, a validated instrument with high reliability and validity, has been used for studies on medication adherence among diabetes patients in many countries 19,30,31 . In Nigeria, the MMAS has been used for studies on medication adherence among hypertensive and psychiatric patients 32,33 .…”
Section: Study Instrumentmentioning
confidence: 99%